Remobilization of Phytol from Chlorophyll Degradation Is Essential for Tocopherol Synthesis and Growth of Arabidopsis. Issue 10 (9th October 2015) - vom Dorp, Katharina; Hölzl, Georg; Plohmann, Christian; Eisenhut, Marion; Abraham, Marion; Weber, Andreas P.M.; Hanson, Andrew D.; Dörmann, Peter
Abstract : Tocopherol synthesis and growth of Arabidopsis require the activity of the phytyl-phosphate kinase VTE6 in the phosphorylation cascade of the phytol salvage pathway. Abstract: Phytol from chlorophyll degradation can be phosphorylated to phytyl-phosphate and phytyl-diphosphate, the substrate for tocopherol (vitamin E) synthesis. A candidate for the phytyl-phosphate kinase from Arabidopsis thaliana (At1g78620) was identified via a phylogeny-based approach. This gene was designated VITAMIN E DEFICIENT6 ( VTE6 ) because the leaves of the Arabidopsis vte6 mutants are tocopherol deficient. The vte6 mutant plants are incapable of photoautotrophic growth. Phytol and phytyl-phosphate accumulate, and the phytyl-diphosphate content is strongly decreased in vte6 leaves. Phytol feeding and enzyme assays with Arabidopsis and recombinant Escherichia coli cells demonstrated that VTE6 has phytyl-P kinase activity. Overexpression of VTE6 resulted in increased phytyl-diphosphate and tocopherol contents in seeds, indicating that VTE6 encodes phytyl-phosphate kinase. The severe growth retardation of vte6 mutants was partially rescued by introducing the phytol kinase mutation vte5 . Double mutant plants ( vte5 vte6 ) are tocopherol deficient and contain more chlorophyll, but reduced amounts of phytol and phytyl-phosphate compared with vte6 mutants, suggesting that phytol or phytyl-phosphate are detrimental to plant growth. Therefore, VTE6 represents the missing phytyl-phosphate kinase, linking phytol release from chlorophyll with tocopherol synthesis. Moreover, tocopherol synthesis in leaves depends on phytol derived from chlorophyll, not on de novo synthesis of phytyl-diphosphate from geranylgeranyl-diphosphate.